Membangun Desa Sehat dan Lestari Melalui Sinergi Kesehatan dan Pertanian Berkelanjutan di Desa Cingkam - Asniati, Asniati; Thoriq, Amrullah; Ismail, Ismail; Mirdayu, Mirdayu; Helnamaulida, Helnamaulida; Mellya, Delvi; Cahyani, Rada Afnida; Jalil, Ivon (Mitra Abdimas: Jurnal Pengabdian kepada Masyarakat, 2024)
This research aims to analyze community empowerment programs through the development of agricultural products and local crafts in Cingkam Village, Gunung Meriah District, Aceh Singkil Regency. The research focuses on the production of organic fertilizers (solid and liquid), banana chip processing, and pandanus mat crafts as efforts to improve the community's economy. The study employs a descriptive qualitative method with data collection techniques through interviews, observation, and documentation. The program was implemented through Community Service Program (KKN) of Teuku Umar University in August 2024. The results indicate that the empowerment program has a positive impact on increasing community knowledge and economy. The production of organic fertilizer made from banana stem waste and rice washing water has been successfully implemented. The development of small and medium enterprises (SMEs) in melted banana chips and pandanus mat crafts has become an alternative source of additional income, particularly for women. It can be concluded that this local potential-based empowerment program is effective in improving the living standards of the Cingkam Village community.